PENGEMBANGAN KOMPETENSI LITERASI DINI PADA ANAK USIA 4-6 TAHUN DENGAN BERMAIN KAWALI (KARTU WARNA LITERASI) DI KELOMPOK BERMAIN PUTRA DHARMA - Monica Arningsari; Lina Putriyanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The purpose of writing this article is to introduce playing Literacy Color Cards (KAWALI) as an effort to build early literacy in learning for children aged 4-6 years. There are still many who think that early literacy in PAUD is just learning to read, so if a PAUD institution has provided a reading corner and a variety of reading books, then it can be said that PAUD has developed early literacy. One strategy that can build early literacy for children aged 4-5 years in PAUD is by playing literacy color cards.